Writing mathematical ecology: A guide for authors and readers. Issue 8 (16th August 2021) - Shoemaker, Lauren G.; Walter, Jonathan A.; Gherardi, Laureano A.; DeSiervo, Melissa H.; Wisnoski, Nathan I.
Abstract: Mathematical techniques have a long and rich history in ecology, often serving as a virtual laboratory to test hypotheses, generate novel predictions, and investigate underlying ecological mechanisms. Recently, novel simulation techniques, advances in computing power, and numerical methods for implementing statistical models have significantly advanced our ability to integrate empirical and theoretical ecology. However, a divide still remains between mathematical and empirical studies, their readership, and integration into the broader literature. Because insights from mathematical ecology are far more general than the techniques employed, limitations in communicating mathematical advances to a broad spectrum of ecologists have arguably hindered ecology's progress, particularly in confronting theoretical predictions with empirical experiments and data. Here, we present a guide for both authors and readers of mathematical ecology, with the aim of increasing the accessibility of mathematical ecology for a broad group of ecologists. We provide a list of best practices when both writing and reading mathematical ecology, incorporating examples from this Special Feature of Ecosphere . This guide complements current guides for writing science, focusing specifically on effective communication of mathematics.